The total art of Stalinism avant-garde, aesthetic dictatorship, and beyond - Grojs, Boris 1947- (Verso Books, 2011)
"From the ruins of Soviet communism, Boris Groys emerges to provoke our interest in the aesthetic goals of its founders. Like modernists elsewhere, the totalitarian artists and theorists of the USSR longed for an art that could transform the world it once sought only to depict. The revolutionaries of October 1917 promised to create a society that was not only more just and more economically stable but also more beautiful, and they intended that the entire life of the nation be completely subordinate to Communist Party leaders commissioned to regulate, harmonize, and create a single artistic whole out of even the most mundane aspects of existence. What were the origins of this idea? And what were its artistic and literary ramifications? In addressing these issues, Groys questions the view that socialist realism was an art for the masses. In this new edition for Verso, Groys revisits the debate that the book has stimulated since its first publication". --amazon.com
Includes bibliographical references (p. [131]-136)
Keywords: Stalin, Josif Vissarionovič -- 1878-1953; Geschichte 1930-1950; Geschichte; Arts / Related to / Politics / History; Union of Soviet Socialist Republics; Socialist realism in art / Soviet Union; Art, Soviet; Totalitarisme; Sociaal realisme; Avant-garde; Stalinisme; Art / URSS.; Kunst; Künste; Sozialistischer Realismus; Kultur; Kunstsoziologie; Sowjetunion